Integrated modeling of nature’s role in human well-being: A research agenda - Rebecca Chaplin-Kramer; Stephen Polasky; Rob Alkemade; Neil D. Burgess; William W.L. Cheung; Ingo Fetzer; Mike Harfoot; Thomas W. Hertel; Samantha L.L. Hill; Justin Andrew Johnson; Jan H. Janse; Patrick José v. Jeetze; et al. (Global Environmental Change, 2024)

Modelling variation in test sensitivity for monitoring leptospirosis in beef cattle - Geoff Jones; Wesley O. Johnson; Cord Heuer (Preventive Veterinary Medicine, 2023)

Evaluating serological tests for foot-and-mouth disease while accounting for different serotypes and uncertain vaccination status - Geoff Jones; Cord Heuer; Wes Johnson; Douglas Begg; Andrew McFadden; Ashish Sutar; Ronello Abila; Clare Browning; Ginette Wilsden; Anna B. Ludi; Syseng Khounsy; Supatsak Subharat (Preventive Veterinary Medicine, 2023)

Two new parasitic copepods of the family Sphyriidae (Copepoda: Siphonostomatoida) from Australian elasmobranchs - Geoff A. Boxshall; Diane P. Barton; Amy Kirke; Xiaocheng Zhu; Grant Johnson (Systematic Parasitology, 2022)
Two new species of the genus Tripaphylus Richiardi in Anonymous, 1878 (family Sphyriidae) are described from elasmobranch hosts caught as bycatch within the Demersal and Timor Reef Fisheries which operate in the Northern Territory exclusive economic zone. Tripaphylus squidwardi n. sp. was collected from Carcharhinus coatesi Whitley and had a prevalence of 11.6%. Tripaphylus dippenaarae n. sp. was collected from Rhizoprionodon acutus (Rüppell) and had a prevalence of 28.2%. The new species are distinguished from existing congeneric species by the body proportions and shape of the adult female and by the arrangement of lobes on the ventral surface of the cephalothorax.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Seismo-acoustic characterisation of the 2018 Ambae (Manaro Voui) eruption, Vanuatu - Iseul Park; Arthur Jolly; Robin S. Matoza; Ben Kennedy; Geoff Kilgour; Richard Johnson; Esline Garaebiti; Sandrine Cevuard (Bulletin of Volcanology, 2021)
A new episode of unrest and phreatic/phreatomagmatic/magmatic eruptions occurred at Ambae volcano, Vanuatu, in 2017–2018. We installed a multi-station seismo-acoustic network consisting of seven 3-component broadband seismic stations and four 3-element (26–62 m maximum inter-element separation) infrasound arrays during the last phase of the 2018 eruption episode, capturing at least six reported major explosions towards the end of the eruption episode. The observed volcanic seismic signals are generally in the passband 0.5–10 Hz during the eruptive activity, but the corresponding acoustic signals have relatively low frequencies (< 1 Hz). Apparent very-long-period (< 0.2 Hz) seismic signals are also observed during the eruptive episode, but we show that they are generated as ground-coupled airwaves and propagate with atmospheric acoustic velocity. We observe strongly coherent infrasound waves at all acoustic arrays during the eruptions. Using waveform similarity of the acoustic signals, we detect previously unreported volcanic explosions at the summit vent region based on constant-celerity reverse-time-migration (RTM) analysis. The detected acoustic bursts are temporally related to shallow seismic volcanic tremor (frequency content of 5–10 Hz), which we characterise using a simplified amplitude ratio method at a seismic station pair with different distances from the vent. The amplitude ratio increased at the onset of large explosions and then decreased, which is interpreted as the seismic source ascent and descent. The ratio change is potentially useful to recognise volcanic unrest using only two seismic stations quickly. This study reiterates the value of joint seismo-acoustic data for improving interpretation of volcanic activity and reducing ambiguity in geophysical monitoring.

Nitrogen fertilizer promotes the rice pest Nilaparvata lugens via impaired natural enemy, Anagrus flaveolus, performance - Pingyang Zhu; Xusong Zheng; Hongxing Xu; Anne C. Johnson; Kong Luen Heong; Geoff M. Gurr; Zhongxian Lu (Journal of Pest Science, 2020)

Nitrogen fertilization of rice plants improves ecological fitness of an entomophagous predator but dampens its impact on prey, the rice brown planthopper, Nilaparvata lugens - Pingyang Zhu; Xusong Zheng; Hongxing Xu; Anne C. Johnson; Kong Luen Heong; Geoff M. Gurr; Zhongxian Lu (Journal of Pest Science, 2020)

Natural enemy enhancement and botanical insecticide source: a review of dual use companion plants - Blankson W. Amoabeng; Anne C. Johnson; Geoff M. Gurr (Applied Entomology and Zoology, 2019)

Discrimination and Variance Structure of Trace Element Signatures in Fe-Oxides: A Case Study of BIF-Mineralisation from the Middleback Ranges, South Australia - Marija Dmitrijeva; Andrew V. Metcalfe; Cristiana L. Ciobanu; Nigel J. Cook; Max Frenzel; William M. Keyser; Geoff Johnson; Kathy Ehrig (Mathematical Geosciences, 2018)

Quantifying the respective and additive effects of nectar plant crop borders and withholding insecticides on biological control of pests in subtropical rice - Pingyang Zhu; Xusong Zheng; Facheng Zhang; Hongxing Xu; Yajun Yang; Guihua Chen; Zhongxian Lu; Anne C. Johnson; Geoff M. Gurr (Journal of Pest Science, 2018)

Comparative study on responses of cattle and water buffalo (Bubalus bubalis) to experimental inoculation of Brucella abortus biovar 1 by the intraconjunctival route—a preliminary report - Abiodun A. Adesiyun; Geoff T. Fosgate; Anil Persad; Mervyn Campbell; Ravi Seebaransingh; Alva Stewart-Johnson (Tropical Animal Health and Production, 2010)

Measurement of retinal vascular tortuosity and its application to retinal pathologies - Geoff Dougherty; Michael J. Johnson; Matthew D. Wiers (Medical & Biological Engineering & Computing, 2010)